Unraveling the tripartite interaction of volatile compounds of Streptomyces rochei with grain mold pathogens infecting sorghum - Sudha, A.; Durgadevi, D.; Archana, S.; Muthukumar, A.; Suthin Raj, T.; Nakkeeran, S.; Poczai, Peter; Nasif, Omaima; Ansari, Mohammad Javed; Sayyed, R. Z. (Frontiers in Microbiology, 2022)
Sorghum is a major grain crop used in traditional meals and health drinks, and as an efficient fuel. However, its productivity, value, germination, and usability are affected by grain mold, which is a severe problem in sorghum production systems, which reduces the yield of harvested grains for consumer use. The organic approach to the management of the disease is essential and will increase consumer demand. Bioactive molecules like mVOC (volatile organic compound) identification are used to unravel the molecules responsible for antifungal activity. The Streptomyces rochei strain (ASH) has been reported to be a potential antagonist to many pathogens, with high levels of VOCs. The present study aimed to study the inhibitory effect of S. rochei on sorghum grain mold pathogens using a dual culture technique and via the production of microbial volatile organic compounds (mVOCs). mVOCs inhibited the mycelial growth of Fusarium moniliforme by 63.75 and Curvularia lunata by 68.52%. mVOCs suppressed mycelial growth and inhibited the production of spores by altering the structure of mycelia in tripartite plate assay. About 45 mVOCs were profiled when Streptomyces rochei interacted with these two pathogens. In the present study, several compounds were upregulated or downregulated by S. rochei, including 2-methyl-1-butanol, methanoazulene, and cedrene. S. rochei emitted novel terpenoid compounds with peak areas, such as myrcene (1.14%), cymene (6.41%), and ç-terpinene (7.32%) upon interaction with F. moniliforme and C. lunata. The peak area of some of the compounds, including furan 2-methyl (0.70%), benzene (1.84%), 1-butanol, 2-methyl-(8.25%), and myrcene (1.12)%, was increased during tripartite interaction with F. moniliforme and C. lunata, which resulted in furan 2-methyl (6.60%), benzene (4.43%), butanol, 2-methyl (18.67%), and myrcene (1.14%). These metabolites were implicated in the sesquiterpenoid and alkane biosynthetic pathways and the oxalic acid degradation pathway. The present study shows how S. rochei exhibits hyperparasitism, competition, and antibiosis via mVOCs. In addition to their antimicrobial functions, these metabolites could also enhance plant growth.